MODULAR CONSORTIUM (MC) AND INDUSTRIAL CONDOMINIUM (IC) IN BRAZIL’S AUTOMOTIVE INDUSTRY - Hasegawa, Haroldo Lhou; Venanzi, Délvio; da Silva, Orlando Roque (Brazilian Journal of Operations & Production Management, 2015)
This paper aims to analyze the benefits of Modular Consortium (MC) and Industrial Condominium (IC) adopted by four auto makers located on Brazil, using exploratory case study conducted in 2013. The key element of success for modern companies or in other words, modern management is the alignment of operation strategy with production practice. It was concluded that although both of models have a positive impact of competitive priority like quick decision making in the production process, gains in stock level reduction and integration of the physical flow and information between the manufacturer and suppliers. On the other hand both of models have negative impact like loss of flexibility in case of a change in suppliers and logistics and problems that may arise as a result of modulists producing modules in other factories.